2019
DOI: 10.1016/j.neuroimage.2018.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Music processing in preterm and full-term newborns: A psychophysiological interaction (PPI) approach in neonatal fMRI

Abstract: A B S T R A C TNeonatal Intensive Care Units (NICU) provide special equipment designed to give life support for the increasing number of prematurely born infants and assure their survival. More recently NICU's strive to include developmentally oriented care and modulate sensory input for preterm infants. Music, among other sensory stimuli, has been introduced into NICUs, but without knowledge on the basic music processing in the brain of preterm infants. In this study, we explored the cortico-subcortical music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 50 publications
(47 reference statements)
3
51
0
2
Order By: Relevance
“…; Lordier et al. ). The personalized music interventions to preterm infants have been shown to restore the functional connectivity between the salience network and auditory, sensorimotor, frontal, thalamus and precuneus networks, resulting in brain networks organization more similar to that of full‐term infants, suggesting that music prevents deficits in brain circuitry in preterm infants and may improve future socio‐cognitive function (Lordier et al.…”
Section: Imaging the Origins Of Neurodevelopmental Disabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…; Lordier et al. ). The personalized music interventions to preterm infants have been shown to restore the functional connectivity between the salience network and auditory, sensorimotor, frontal, thalamus and precuneus networks, resulting in brain networks organization more similar to that of full‐term infants, suggesting that music prevents deficits in brain circuitry in preterm infants and may improve future socio‐cognitive function (Lordier et al.…”
Section: Imaging the Origins Of Neurodevelopmental Disabilitymentioning
confidence: 97%
“…It is now well established that the environment and the neurosensory stimuli have an impact on sensorimotor, cognitive and psychological development, particularly during the neonatal period, and fMRI and EEG are valid methods to study early functional competence of the developing brain (Adam‐Darque et al. ; Lordier et al., ). Only just emerging though is the impact of sensory stimuli and general cellular activity on interneuron survival and distribution within the cortex (Denaxa et al.…”
Section: Imaging the Origins Of Neurodevelopmental Disabilitymentioning
confidence: 99%
“…A recent study of 35, <32 weeks GA neonates revealed that those who listened to 8 min of pre-composed music five times per week, based on nursing assessment of developmental need (assessed on a neonatal behavioral assessment scale), timed to be offered at the moment and distinctly related to need of sleep, wakefulness-interactive, or at a time of alertness, such as prior to feeding, led to functional brain architectures (shown through fMRI) that were more similar to those of full-term newborns (Lordier et al, 2019). This provided their evidence for a ''beneficial effect of music on the preterm brain.''…”
Section: Musical Parameters Timingmentioning
confidence: 99%
“…Recent research has evaluated the effects of music training with benefits that have attributed music learning as a significant contributor to the improvement of cognitive function (Barrett et al, 2013). In particular, music's implicit audio-structural capacity (Lordier et al, 2019) seems to reflect notable influence in both developmental outcomes and restorative capabilities that stretch across the lifespan. While numerous studies have focused on outcomes of young children (Trainor et al, 2012;Moreno et al, 2011) and aging adults (Johnson et al, 2011), few have considered the impact of the pre-natal 'sound' environment in terms of ritual and context, nor the culturally relevant conditions and applications that organized purposeful sounds and music may stimulate.…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.1101/19011874 doi: medRxiv preprint Fontana C., Marasca F., et al demonstrated to improve brain maturation, as assessed by magnetic resonance imaging (MRI), and neurodevelopmental outcomes (24)(25)(26). More recently, Early Intervention strategies, based on a multisensory stimulation approach, have been shown to promote infants' visual acuity, neurobehavior and brain development (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%